The vision of the nursing team regarding their records - Lorena Mara Nóbrega de Azevêdo; Aline Galúcio de Oliveira; Fernanda Aparecida Soares Malveira; Cecília Nogueira Valença; Edilma de Oliveira Costa; Raimunda Medeiros Germano (Rev Rene)
The aim of this research was to know the perception of nurses about their records and how they are performed. It is a Descriptive exploratory research, with qualitative approach, performed at the University Hospital Onofre Lopes in Natal/RN, with 15 professional of the nursing team. The data collection occurred with semi-structured interviews submitted to thematic content analysis. It was identified that the professionals perceive their records as an indispensable tool in the service, whose functions embrace communication, legal backing and evaluation of their work. In its content there is information about procedures performed and there is little description of the emotional aspects. Then, it was found out that the nursing records are consolidated into just a moment of documentation, with distortion between this concept and the evolution of nursing. Nursing professionals understand the importance, functions and content of their records, however, it is still necessary some improvement in their production.